Islamization In Besemah During The 18th to 20th Centuries - Rahyu Zami (Criksetra: Jurnal Pendidikan Sejarah, 2024)
Abstract: The arrival of Islam to the Besemah region is less certain, but the character of a cleric named Puyang Awak is considered the first spreader of Islam in Besemah.  Islam came to Besemah rather late considering that this region is an inland area that is quite difficult to access, but this situation did not make the development of Islam experience a significant obstacle, especially by making Islam the official religion of the Sultanate of Palembang. This research method uses historical method, which consists of heuristic, verification, interpretation and historiography. The research findings show that the massive development of Islam was seen since Palembang became the centre of Islamic studies by producing great scholars in the 18th century. The success of the spread of Islam in Besemah is inseparable from the da'wah strategy applied by mubaligh which is polite and accommodating to the existing local culture. The support of Islamic organizations such as Sarekat Islam and Muhammadiyah is one of the supporting factors for the successful spread of Islam and the purification of Islam in the Besemah region. Abstrak: Kedatangan Islam ke wilayah Besemah kurang diketahui secara pasti, namun ketokohan seorang ulama bernama Puyang Awak dianggap penyebar pertama Islam di Besemah.  Islam datang ke Besemah agak terlambat melihat wilayah ini termasuk wilayah pedalaman yang cukup sulit untuk diakses, namun keadaan tersebut tidak membuat perkembangan agama Islam mengalami suatu kendala yang berarti, terutama dengan dijadikan Islam sebagai agama resmi kesultanan Palembang. Metode peneitian ini menggunakan metode historis, yang terdiri dari heuristik, verifikasi, interpretasi dan historiografi. Temuna penelitian menunjukkan perkembangan Islam secara massif tampak sejak Palembang menjadi pusat studi Islam dengan melahirkan ulama-ulama besar di abad 18 Masehi. Keberhasilan penyebaran Islam di Besemah tidak terlepas dari strategi dakwah yang diterapkan oleh mubaligh yang bersifat santun dan akomodatif terhadap budaya lokal yang ada. Dukungan organisasi Keislmana seperti Sarekat Islam dan Muhammadiyah menjadi salah satu faktor pendukung suksesnya penyebaran Islam dan pemurnian Keislaman di wilayah Besemah.